Bioleaching of chalcopyrite by UV-induced mutagenized Acidiphilium cryptum and Acidithiobacillus ferrooxidans - 徐爱玲 夏金兰 张帅 杨宇 聂珍嫒 邱冠周 (Transactions of Nonferrous Metals Society of China, 2010)
The original strains Acidithiobacillusferrooxidans GF and Acidiphilium cryptum DXI-1 were isolated from the drainage of some caves riched in chalcopyrite in Dexing Mine in Jiangxi Province of China. The optimum temperature and pH for growth were 30 ℃ and 3.5 for Ac. cryptum DXI-1, and 30 ℃ and 2.0 for At. ferrooxidans GF, respectively. For Ac. cryptum DXI-1, the optimum UV radiating time was 60 s and the positive mutation rate was 22.5%. The growth curves show that Ac. cryptum after mutagenesis reached stationary phase within 60 h, which was 20 h earlier than the original strain. For At. ferrooxidans GF, the optimum mutation time was 60 s and the positive mutation rate was 35%. The most active UV-mutated strain At. ferrooxidans GF oxidized all the ferrous after 48 h. The bioleaching experiments showed that bioleaching with the mixture of UV-mutated strains of At. ferrooxidans GF and A c. cryptum DX1-1 （1：1） could extract 3.01 g/L of copper after 30 d, while the extracted copper was 2.63 g/L with the mixture of the original strains before UV-mutation. At the end of the bioleaching experiments, the proportion of the cell density in the cultures ofAc. cryptum DXI-1 andAt.ferrooxidans GF was approximately 1：5.